Answer:
f - 1 (x) = - x6 - 76
Step-by-step explanation:
Since g(f(x))=x g ( f ( x ) ) = x , f−1(x)=−x6−76 f - 1 ( x ) = - x 6 - 7 6 is the inverse of f(x)=−6x−7 f ( x ) = - 6 x - 7 .
You didn't give the multiple choice so no one can help you do make sure to include that next time
Answer:
c
Step-by-step explanation:
reason for is because when you add all the like terms you end up with c
Answer: A (-2, 3)
Step-by-step explanation:
1. To know which oredered pairs does not lie on the graph, you must substitute the x-coordinate of each one of thm into the function and if you obtain the y-coordinate shown in that ordered pair, then that point lies on the graph.
2. Therefore, you have:
A. x=-2
(It does not lie on the graph).
B. x=--1
(It lies on the graph).
C. x=3
(It lies on the graph).
D. x=4
(It lies on the graph).
Therefore, the answer is the option A.